The formal notice of persons - Arsene, Ionela (Technium Social Sciences Journal, 2023)
The public order policeman is a civilian, armed civil servant, with a special status, who usually wears a uniform and performs the duties provided by law for the Romanian Police, as a specialized institution of the state. The policeman exercises his function by officially intervening, when the situation requires it, against any individual, regardless of his rank or social position. Any action taken must be motivated by the need to defend the life and bodily integrity of the individual, but also the property, or to maintain the climate of public safety. In the interaction with the citizens, various situations have been noticed in which the police officers do not address them with sufficient kindness, they apply the legal provisions abusively and even commit acts of impropriety, things incompatible with the status of a police officer or, even better said, the status of the police from a member country of the European Union. The job of a policeman, due to its specificity, comes with special duties and risks, so that through the law on the organization and operation of the Romanian Police and the Statute of the policeman, he is granted rights and obligations by which he can fulfill his entrusted missions, taking at the same time in calculating and ensuring protection. Precisely in order to carry out everything according to the legal provisions and for the safety of people, during and in connection with the fulfillment of the duties, the policeman is invested with public authority. As a result of the usual activities, the operational staff of the Romanian Police may face several situations that can only be solved by means of the laws in force and based on the experience gained. That is why it is necessary to know and respect the methods of intervention by applying appropriate rules, the intervention being an imperative condition for the successful fulfillment of professional duties.